"It Makes You Feel Good to Help!": An Exploratory Study of the Experience of Peer Mentoring in Long-Term Care. Issue 3 (11th September 2022) - Theurer, Kristine A.; Stone, Robyn I.; Suto, Melinda J.; Timonen, Virpi; Brown, Susan G.; Mortenson, W. Ben
Abstract: Social isolation and loneliness in long-term care settings are a growing concern. Drawing on concepts of social citizenship, we developed a peer mentoring program in which resident mentors and volunteers formed a team, met weekly for training, and paired up to visit isolated residents. In this article, we explore the experiences of the resident mentors. As part of a larger mixed-methods study conducted in 10 sites in Canada, we interviewed mentors ( n = 48) and analysed data using inductive thematic analysis. We identified three inter-related themes: Helping others, helping ourselves described the personal benefits experienced through adopting a helping role; Building a bigger social world encapsulated new connections with those visited, and; Facing challenges, learning together described how mentors dealt with challenges as a team. Our findings suggest that a structured approach to mentoring benefits residents and helps them feel confident taking on a role supporting their isolated peers.